The Salt Lake papers : from the years in the earthscapes of Utah - Lueders, Edward, 1923- (The University of Utah Press, 2018)
"Cast in the companionable journal-notebook style that readers enjoyed in Lueders's 1977 classic The Clam Lake Papers, this new collection of essays, The Salt Lake Papers, follows the author's move from the north woods of Wisconsin to the Intermountain West of Utah. The volume is divided into two sections by location and time. Book One reflects the central geophysical presence of Great Salt Lake, in view from the author's home and the University of Utah campus where he studied and taught. Researched and composed during the 1980s, it is published here for the first time. Book Two ensues with his retirement to the "earthscapes" of the Torrey Capitol Reef area of southern Utah and contemplates the Colorado River system. Hydrology thus provides both the physical and the metaphysical basis for the author's reflective insights and for the natural grounding it gives his advancing thought."--Provided by publisher.